(untitled) (Research, Society and Development, 2020)
The placement of implants in the maxilla has different characteristics from those found in the mandible. One of the most frequent challenges in the installation of implants is atrophy of the maxilla after partial or total loss of dental units. As a result, there is a significant decrease in the height and volume of the bone available in the posterior region of the maxilla. Currently, several techniques are used to improve bone quality and, consequently, the primary stability of the implant, from the established techniques such as Summers bone expansion technique, through osteotomes, and the most recent ones, such as osseodensification through Densah Bur® multilaminated drills, which consists of the condensation of the bone tissue walls made during preparation. The objective of the study was to present a clinical case using the osseodensification technique in the atrophic maxilla, for later installation of dental implants in the maxilla without using the Summers technique and bone grafts. After implant placement, Osstell® was used to assess primary stability. We conclude that osseodensification is a new biomechanical preparation technique that maintains the integrity of the alveolar ridge and allows the placement of implants with greater primary stability, allows for less morbidity and less time for completion of the rehabilitation treatment.